Answer:
10 (3 x - 1)
Step-by-step explanation:
Answer:
The answer would be B
Step-by-step explanation:
Since you are starting out, you can make that a one, so then subtract that one by how much candy you ate (1/8 and 1/4)
Answer:
Step-by-step explanation:
9). -2.2(4 - 1.9x) = 3.3(0.2x - 0.8)
-8.8 + 2.2(1.9x) = 0.66x - 2.64
-8.8 + 4.18x = 0.66x - 2.64
4.18x - 0.66x = 8.8 - 2.64
3.52x = 6.16
x = 1.75
10). 3.2(1 + 2.6x) = 2.4(x - 3.6)
3.2 + 8.32x = 2.4x - 8.64
8.32x - 2.4x = -3.2 - 8.64
5.92x = -11.84
x = 2
11). 4.6(2x - 5.5) = 3.9 + 0.8(1 + 5.5x)
9.2x - 25.3 = 3.9 + 0.8 + 4.4x
9.2x - 25.3 = 4.7 + 4.4x
9.2x - 4.4x = 25.3 + 4.7
4.8x = 30
x = 6.25
12). 0.2(3x + 2.5) - 4.9 = 3.8 - 2.2(x - 5.5)
0.6x + 0.5 - 4.9 = 3.8 - 2.2x + 12.10
0.6x - 4.4 = -2.2x + 15.90
0.6x + 2.2x = 15.90 + 4.4
2.8x = 20.30
x = 7.25
Step-by-step explanation:
Hey there!
Given;
The points is; (-1 , 2) and slope is 4.
<em>Note:</em><em> </em><em>Use </em><em>one-point</em><em> formula</em><em>.</em>
<em>
</em>
<em>~</em><em> </em><em>Put </em><em>all</em><em> values</em><em>.</em>
![(y - 2) = 4(x + 1)](https://tex.z-dn.net/?f=%28y%20-%202%29%20%3D%204%28x%20%2B%201%29)
~ Simplify it.
![(y - 2) = 4x + 4](https://tex.z-dn.net/?f=%28y%20-%202%29%20%3D%204x%20%2B%204)
![4x - y + 6 = 0](https://tex.z-dn.net/?f=4x%20-%20y%20%2B%206%20%3D%200)
Therefore, the required equation is; 4x-y+6=0.
<h3>
<em><u>Hope</u></em><em><u> it</u></em><em><u> helps</u></em><em><u>.</u></em><em><u>.</u></em><em><u>.</u></em></h3>
Answer: (not enough information) Is there a picture that goes along with the problem?
Step-by-step explanation: